2000
DOI: 10.1159/000028358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nabumetone Treatment on Vascular Responses of the Thoracic Aorta in Rat Experimental Arthritis

Abstract: Nabumetone is a nonsteroidal anti-inflammatory (NSAI) drug which is known to cause less gastrointestinal damage than other NSAI drugs. This study was performed to evaluate whether nabumetone treatment might alter the vascular aberrations related to inflammation in a rat model of adjuvant-induced arthritis. Nabumetone treatment (120 or 240 mg·kg–1·day–1, orally) was initiated on the 15th day of adjuvant inoculation and continued for 14 days. Arthritic lesions, vascular contractile and rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
4
11
1
1
Order By: Relevance
“…In the present study, we investigated endothelial function in the AIA model, which is commonly accepted as having many histologic and clinical features in common with human RA (31) and which is widely used to predict clinical efficacy of new therapies in RA (32). In accordance with previous studies (12)(13)(14)(15)(16)(33)(34)(35), our data show that endothelial function assessed by the vasodilating response to ACh is impaired in AIA rats. We also demonstrated that endothelial dysfunction correlates with disease activity.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, we investigated endothelial function in the AIA model, which is commonly accepted as having many histologic and clinical features in common with human RA (31) and which is widely used to predict clinical efficacy of new therapies in RA (32). In accordance with previous studies (12)(13)(14)(15)(16)(33)(34)(35), our data show that endothelial function assessed by the vasodilating response to ACh is impaired in AIA rats. We also demonstrated that endothelial dysfunction correlates with disease activity.…”
Section: Discussionsupporting
confidence: 79%
“…There are limited previous reports of endothelial dysfunction associated with arthritis in animal models. All currently reported studies have utilized the rat model of adjuvant-induced arthritis [7,8,30,31,32,38]. As such, this study represents the first report of endothelial dysfunction in a large animal model, and also the first in a collagen-induced arthritis model.…”
Section: Discussionmentioning
confidence: 91%
“…It is noteworthy that the ED severity mirrors the arthritis severity. Indeed, at day 24 post-injection in AIA, no alteration of ACh-induced relaxation was found in grade 1 arthritic rats whereas rats with grade 2 or 3 arthritis exhibited a reduced relaxation to ACh [16]. Likewise, at day 35 post-injection, we identified an inverse correlation between the maximal effect of ACh and the arthritis grade [22].…”
Section: Endothelial Dysfunction In Animal Models Of Arthritismentioning
confidence: 99%